Pengembangan Multimedia Pembelajaran Interaktif Materi Pokok Sistem Tata Surya Untuk Siswa Kelas VI SD - Melinda, Vannisa Aviana; Sambung, Dimas; Ningrum, Dian Eka Aprilia Fitria; Erfantinni, Imroatul Hayyu; Febriani, Roiyan One (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2018)
The objective of the research and development to produce a multimedia interactive learning product are valid so that it can be used as a learning resource that is effective and compelling subject matter for the solar system of elementary class VI. Research and development model used adapted from multimedia development Lee and Owens model. Multimedia interactive learning is validated by 1-person expert in material and 1-person expert in media, then individual tests by 2 people, small group of trials by 4 people and field test as many as 10 people. After the validation of results, the analysis method for multimedia interactive learning was declared valid by summing up the results of the calculations of experts, material and media students.